A NEW VISION OF THE BRAZILIAN RESEARCH: THE KNOWLEDGE AND PEDAGOGICAL PRACTICES IN TEACHER TRAINING - Tonni da Silva, Yvison; Tolentino de Almeida, Diomedes; Tolentino Filho, Dorgival; Paulo Pereira, Rosimary (Revista Gênero e Interdisciplinaridade, 2025)
This article aimed to understand a new vision of Brazilian research: the knowledge and pedagogical practices in teacher training, contributing to The enrichment and the strengthening in the formation of the pedagogical practice, resulting essentially in the construction of new knowledge in the teaching work. In this context, the relationship between pedagogical practice and professional experience is discussed first. Secondly, consideration is given to knowledge and pedagogical practices in teacher training, and consequently, aspects that may influence the development of the formation of pedagogical practice in the professional experience of the teacher. Finally, the study concludes that the professional development of the teacher is related to the pedagogical training and the knowledge acquired in the course of his life, especially those coming from professional experience.